External assessor for the tenure of a faculty member at the Technological Educational Institute of Thessaloniki, Department of Business Management - Tsapatsoulis, Nicolas (My University, 2026)
External assessor for the tenure of a faculty member at the Technological Educational Institute of Thessaloniki, Department of Business Management